English Influence on the Structure of Igbo Personal Names - Chukwuma Livinus Ndububa (Lembaga Yasin AlSys, 2026)
English–Igbo language contact increasingly shapes contemporary personal naming practices in Igboland, where English functions as both a second and an official language. This study examines the phonological and morphological structures of English-influenced Igbo personal names and investigates how these transformations reflect patterns of language contact and changing naming conventions among Igbo speakers. Grounded in Language Contact Theory, the study employed a qualitative descriptive design and thematic analysis to examine 68 purposively selected Igbo personal names. The findings reveal that English influence produces phonological modifications involving vowel substitution, stress shifts, and tone loss. Morphological adaptations include derivation, respelling, truncation, gemination, orthographic addition, and cross-linguistic hybrid formation. These processes demonstrate that sustained contact between English and Igbo is reshaping indigenous personal naming conventions and may affect the cultural and linguistic significance of Igbo names. The study contributes to scholarship on language contact, morphology, phonology, and African onomastics by documenting the structural mechanisms through which English influences Igbo personal names. It further underscores the need to preserve traditional Igbo onomastic practices and recommends that Igbo language planners intensify efforts to promote standard orthography and pronunciation to limit unnecessary alterations of indigenous names. Future research may extend this inquiry to the syntactic, semantic, pragmatic, and sociocultural motivations underlying the adoption of English-influenced naming forms.